The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.2514/3.12736
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of fluctuating pressure loads in shock/boundary-layer interactions using vortex generators

Abstract: Fluctuating wall pressure measurements have been made in a separated shock wave/turbulent boundary-layer interaction produced by an unswept compression corner in a Mach 5 flow. Wheeler doublet vortex generators were placed upstream of the corner to study their effect on the fluctuating pressure loads within the interaction. The vortex generators produce significant three dimensionality in an otherwise two-dimensional interaction. They reduce the upstream influence and the length of the region of separation sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 15 publications
(2 reference statements)
1
34
0
Order By: Relevance
“…A velocity deficit is present downstream of the vertices of each ramp, consistent with results found at free-stream Mach numbers ranging from 1.5 to 5 by Barter and Dolling [12] and Holden and Babinsky [16]. Conversely, Pitt Ford and Babinsky [13] reported that close to the wall at y/δ = 0.1, the mean velocity is highest downstream of a vertex; a discrepancy that is tentatively linked to differences in vortex migration due to different characteristics of the boundary layer (see [9]).…”
Section: Mean Flow Organizationsupporting
confidence: 78%
See 1 more Smart Citation
“…A velocity deficit is present downstream of the vertices of each ramp, consistent with results found at free-stream Mach numbers ranging from 1.5 to 5 by Barter and Dolling [12] and Holden and Babinsky [16]. Conversely, Pitt Ford and Babinsky [13] reported that close to the wall at y/δ = 0.1, the mean velocity is highest downstream of a vertex; a discrepancy that is tentatively linked to differences in vortex migration due to different characteristics of the boundary layer (see [9]).…”
Section: Mean Flow Organizationsupporting
confidence: 78%
“…The micro-ramp is one particular type of SBVGs, which has been shown to reduce the length of the separated region, causing a more abrupt pressure rise (see, e.g., [11][12][13]), as well as a stabilization of the interaction region [14]. Although experimental studies (see [15,16]) suggest that vane-type SBVGs may be more effective in suppressing separation, micro-ramps offer the advantage of being more rugged, therefore less subject to mechanical failure, which is essential for engine intake applications.…”
Section: Introductionmentioning
confidence: 99%
“…Their typical height is about 50% of the boundary layer thickness and their effectiveness comes from the two counter-rotating vortices it introduces in the flow [4]. These vortices transport high-momentum fluid towards the wall, thus creating a fuller boundary layer profile, allowing the flow to pass through the shock system with less separation [5][6][7][8]. Anderson et al [9] used Reynolds Averaged Navier Stokes (RANS) simulations to show that micro-ramps can reduce the incompressible shape factor of the incoming boundary layer to the same level as obtainable with boundary layer bleed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the Repds decreases the drag (pressure drop) for the entire ow. Considering this analysis and some methods used to reduce drag on airfoils (Barter and Dolling 1995), the authors propose that the drag in turbulent ows can be reduced by adding vortexes. …”
Section: Mechanism Analysis and Discussionmentioning
confidence: 99%